PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS - Sari, Henny Retno (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Nowadays, the issue regarding the Corporate Social Responsibility (CSR) is growing rapidly. The company is not only being responsible for maximizing its profit but also responsible for its surrounding environment. CSR is one of the actions from the companyâs ethic consideration in order to increase the life quality of employees and their family as well as increasing life of its surrounding society and the society at large. The companyâs size shows either small or big of its sales, employees or the number of asset owned by the company. Profitability describes the companyâs capability to get profit through all the ability and the existing source. The purpose of this research is to find out the influence of Corporate Social Responsibility (CSR) disclosure and companyâs size to the profitability. The research result shows that the CSR disclosure has positive influence to the profitability, while the companyâs size has negative influence to the profitability.Keywords: Corporate Social Responsibility (CSR), Companyâs Size and Profitability.